Alkynyl Fischer Carbenes as a Platform for the Production of Difluorodiazaborinine Complexes via β‐Amino‐azadienes. Issue 38 (10th October 2019) - Benítez‐Puebla, Luis J.; López, Julio; Flores‐Álamo, Marcos; Cruz, David Cruz; Peña‐Cabrera, Eduardo; Delgado, Francisco; Tamariz, Joaquín; Vázquez, Miguel A.
Abstract : The results of a study of the reactivities of alkynyl Fischer carbenes in the syntheses of diazaborinine derivatives 7a‐i are reported. The strategy employed included the use of β‐amino‐α, β‐unsaturated carbenes (3a–j ) with different amines in order to determine the scope of a previously unknown catalytic reaction in the presence of copper salts and anilines. The reaction was highly stereoselective, yielding ( Z )‐isomers of the β‐amino‐1‐azadiene framework as the main products (4a–o ). As an extension of this research, the compounds 4a–o proved to be suitable precursors for the syntheses of diazaborinine scaffolds in good yields (7a‐i ). Abstract : The reactivities of β‐amino‐α, β‐unsaturated Fischer carbenes of Cr(0) in the production of β‐amino‐1‐azadiene scaffolds were investigated. These complexes, functionalized with β‐donor groups, underwent a transmetalation process with copper catalysts as key intermediates, leading to the suggesting of a probable mechanism of reaction. The obtained azadienes were used for the syntheses of difluorodiazaborinines, which are sought as fluorescent materials.